Corporate Governance and Financial Performance in Sharia Banks: An Analysis in Islamic Finance - Arfathan; Winda Sari; Mohammad Hussien (IHSA Institute, 2024)
This research investigates the relationship between corporate governance mechanisms and financial performance in Sharia banks, aiming to provide insights into the governance dynamics and economic outcomes in Islamic finance. Adopting a mixed-methods approach, the study combines quantitative analysis with qualitative insights to examine governance mechanisms such as board composition, transparency measures, and Sharia supervisory board (SSB) independence, and their impact on key financial performance indicators including return on assets (ROA), return on equity (ROE), and non-performing financing (NPF) ratios. Data is collected from publicly available sources and primary data through structured surveys or interviews with stakeholders in Sharia banks. Descriptive statistics, inferential tests, and thematic analysis are employed to analyze the relationships between governance mechanisms and financial performance indicators. The findings reveal significant positive relationships between board composition and financial performance, transparency measures and financial performance, and negative relationships between SSB independence and NPF ratios. The study highlights the importance of robust governance frameworks in promoting financial stability, sustainability, and stakeholder trust in Sharia-compliant institutions. However, limitations including data constraints, contextual specificity, and causality issues are acknowledged, and areas for future research are identified to address these limitations and advance knowledge in Islamic finance governance.